Artificial intelligence-aided materials design : AI-algorithms and case studies on alloys and metallurgical processes /: AI-algorithms and case studies on alloys and metallurgical processes. (2022) - Jha, Rajesh; Jha, B. K (Bimal K.)
No abstract available